MULTIAPPOSITIVES AS THE BONUS INFORMATION FOR THEIR ANCHOR - Hero Gunawan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This article discusses multiappositives as the bonus information for their anchor within the construction of apposition. Therefore, the information related to the anchor becomes adequate. Therefore, the anchor to which the appositives refer will easily be indersood. The bonus information provided in appositives has certain semantic relation. This article uncovers 1) types of multiappositives as the bonus information, 2) semantic relation in a construction of apposition, and 3) sequential patterns of multiappositives as the bonus information. The aims of this research are: 1) to identify and explain types of multiappositives, 2) to describe semantic relation of multiappositives within the construction of apposition, and 3) to analyse the sequential patterns of multiappositives. The data sources are taken from English printed media within three levels of distributional coverage, i.e. national, regional and international. The data analyzed are descriptive in nature, and the data analysis is conducted through employing the method of qualitative research. To analyse such descriptive data, the distributional method of analysis with the use of the following techniques: deleting, extracting, and intruding. The results indicate that: 1) four types of multiappositives as the bonus information are found: a) external multiappositives, b) internally-and-externally-related multiappositives, c) externallyrelated multiappositives, d) externally-and-integrally-related multiappositive, 2) semantic relations found in a construction of apposition cover two types of semantic relations: a) equivalence consisting of four types, namely designation equivalence, reformulation equivalence, and appellative equivalence, and b) attribution, and 3) sequential patterns of multiappositives as the bonus information are: 1) A, A1 , A 2 , A 3 , A 4 , 2) AA1=A2 and A2 = A3 , 3) A = A1 ; A1 = A2 ; A2 = A3 , 4) : A = A1 ; A1 = A2 ; A2 = A3A 4 , where A represents the anchor, while A1 , A2 , A3 , and A4 represent appositives.